PELAKSANAAN PENGAWASAN TERHADAP DEPOT AIR MINUM ISI ULANG DI RW 02 DAN RW 09 KELURAHAN KRAMAT PELA, JAKARTA SELATAN: Supervision Of Refillable Drinking Water Depots In Rw 02 And Rw 09 Of Kramat Pela Urban Village, South Jakarta - Itsnain Umar Hasby; Sharda Abrianti (Faculty of Law, Universitas Trisakti, 2024)
Refillable drinking water depots (DAMIU) offer a practical solution for the community's drinking water needs. However, the condition of DAMIUs that produce drinking water for the community needs to be supervised in accordance with applicable regulations as a form of consumer protection. This study aims to examine the implementation of DAM supervision in RW 02 and RW 09 Kramat Pela Urban Village, South Jakarta, as well as the application of sanctions for DAM business actors who do not comply with standards. The research is conducted socio-legally from regulations and related literature. The analysis is carried out qualitatively with an inductive method. The results of the analysis show that there are DAMs that do not meet the standards, as evidenced by the presence of E.Coli and Coliform bacteria in refill drinking water and violations in the water treatment and distribution process. Lack of supervision by the Puskesmas and related agencies through water quality testing and periodic inspections in accordance with the Minister of Health Regulation No. 2 Year 2023 on the Implementation of Government Regulation No. 66 Year 2014 on Environmental Health is the main problem. The sanction given by the Puskesmas is only a verbal warning, but there is no further evaluation after the sanction is given.